Analysis of Challenges and Solutions in Developing Pedagogical Competence of Prospective Elementary School Teachers: A Systematic Literature Review - Astuti, Yuni Dwi; Rohmani; Yuni Dwi Astuti (Institute of Educational, Research, and Community Service)
Pedagogical competence is an essential foundation for primary school pre-service teachers to conduct high-quality instruction. This study aims to systematically identify the main challenges faced by primary school pre-service teachers in developing pedagogical competence and to analyze effective solutions and strategies that have been implemented. The research method employed is a Systematic Literature Review (SLR) guided by the PRISMA 2020 framework. The data collection process was conducted in June 2025 through the Google Scholar database, with a publication range from 2020 to 2024. Search keywords were formulated using Boolean operators to combine core concepts, such as: (